Voltammetric behaviour of biological macromolecules at arrays of aqueous|organogel micro-interfaces - Scanlon, M.; Strutwolf, J.; Arrigan, Damien (Royal Society of Chemistry, 2010)
The behaviour of two biological macromolecules, bovine pancreatic insulin and hen-egg-whitelysozyme (HEWL), at aqueous-organogel interfaces confined within an array of solid-state membrane micropores was investigated via cyclic voltammetry (CV). The behaviour observed is discussed in terms of possible charge transferring species and mass transport in the interfacial reaction. Comparison of CV results for HEWL, insulin, and the well-characterised model ion tetraethylammonium cation (TEA+) revealed that the biomacromolecules undergo an interfacial reaction comprising biomacromolecular adsorption and facilitated transfer of electrolyte anions from the organic phase to a protein layer on the aqueous side of the interface, whereas TEA+ undergoes a simple ion transfer process. Evidence for biomacromolecular adsorption on the aqueous side of the micro-interfaces is provided by comparison of the CVs for TEA+ ion transfer in the presence and absence of the biomacromolecules. Similar experiments in the presence of the low generation polypropylenimine tetraamine dendrimer, (DAB-AM-4), a smaller synthetic molecule, revealed it to be non-adsorbing. The behaviour of biological macromolecules at miniaturised aqueous-organogel interfaces involves adsorption on the aqueous side of the interface and transfer of organic phase electrolyte anions across the interface to associate with the adsorbed biomacro molecule. The data presented support the previously suggested mechanism forbiomacromolecular voltammetry at liquid-liquid interfaces, involving adsorption and facilitated ion-transfer of organic electrolyte anions.